Using Micro-Credentials to Promote Effective Teacher Professional Development: A Case Study from Xi’an Jiaotong-Liverpool University - Lan Luo; Jian Chen (Adult Education Research Conference, 2023)
This study illuminates the characteristics of micro-credentials, which can effectively meet the needs of working professionals in higher education for teacher professional development and career competence-building.
Keywords: Micro-credentials (MCs); teacher professional development (TPD); higher education (HE)